Effect of gas properties on the dynamics of the electrical slope asymmetry effect in capacitive plasmas: comparison of Ar, H2 and CF4. (1st December 2015) - Bruneau, B; Lafleur, T; Gans, T; O'Connell, D; Greb, A; Korolov, I; Derzsi, A; Donkó, Z; Brandt, S; Schüngel, E; Schulze, J; Diomede, P; et al.
Abstract: Tailored voltage excitation waveforms provide an efficient control of the ion energy (through the electrical asymmetry effect) in capacitive plasmas by varying the 'amplitude' asymmetry of the waveform. In this work, the effect of a 'slope' asymmetry of the waveform is investigated by using sawtooth-like waveforms, through which the sheath dynamic can be manipulated. A remarkably different discharge dynamic is found for Ar, H2, and CF4 gases, which is explained by the different dominant electron heating mechanisms and plasma chemistries. In comparison to Argon we find that the electrical asymmetry can even be reversed by using an electronegative gas such as CF4 . Phase resolved optical emission spectroscopy measurements, probing the spatiotemporal distribution of the excitation rate show excellent agreement with the results of particle-in-cell simulations, confirming the high degree of correlation between the excitation rates with the dominant heating mechanisms in the various gases. It is shown that, depending on the gas used, sawtooth-like voltage waveforms may cause a strong asymmetry.